Postoperative Pain Among Patients After Day-Case Surgery. Issue 4 (October 2017) - Elaqoul, Aqel; Obaid, Abdullah; Yaqup, Eman; Shahen, Ibtesam; Arraqap, Ahmad; Alshatnawi, Iyad; Alnajar, Malek; Al-Momani, Sharaf
Abstract : Postoperative pain occurs at a high incidence after day-case surgery, with many patients reporting moderate to severe pain. A cross-sectional design was used in this study to estimate the prevalence of postoperative pain in the early postoperative period after day-case surgery and to determine whether there is a relationship between demographic and clinical variables. A convenient sample of 300 patients, aged between 18 and 80 years, was selected from all postoperative patients after day-case surgery over a period of 6 months. At the first 2 hr after surgery, about 70% of patients had either no pain or mild pain at rest and about 30% of patients had moderate to severe pain. About one third of these patients (103; 35.8%) reported mild pain, and about 43% of patients had moderate to severe pain on movement in the first 2 hr after surgery. Furthermore, 25.3% and 41.3% of the patients reported moderate to severe pain during the first 24 hr after hospital discharge at rest and on movement, respectively. Female patients had significantly higher pain scores than male patients ( p < .001). Significant decrease in pain scores was reported in the first 2 hr after surgery (mean = 2.2, SD = 2) and within the first 24 hr after discharge (mean = 1.8, SD = 2.2, t (288) = 4.3, p =. 005) at rest. The prevalence of pain among postoperative patients after day-care surgery in Jordan is high. Young adult and female patients have higher pain scores after day-case surgery.